Streptomyces sp. VITGV156 secondary metabolite binds pathogenic protein PBP2a and Beta-lactamase - Pattapulavar, Veilumuthu; Ramanujam, Sathiyabama; Shah, Manisha; Thirunavukkarasu, Muthu Kumar; Arumugam, Sivakumar; Karuppasamy, Ramanathan; Samrot, Antony V.; Deepasree, K.; Venugopal, Subhashree; Christopher, John Godwin (Frontiers in Bioinformatics, 2025)
IntroductionThe genus Streptomyces is renowned for its prolific production of bioactive compounds, including antibiotics and secondary metabolites with pharmaceutical applications. This study focuses on Streptomyces sp. VITGV156, an isolate with promising antimicrobial properties, aiming to characterize its genomic potential and bioactive compounds through computational and experimental analyses.MethodsGenomic sequencing of Streptomyces sp. VITGV156 was performed to identify biosynthetic gene clusters (BGCs) associated with secondary metabolite production. Antimicrobial assays were conducted using crude extracts against Gram-positive and Gram-negative pathogens. Gas Chromatography-Mass Spectrometry (GC-MS) was employed to identify secondary metabolites. Additionally, ADME (Absorption, Distribution, Metabolism, and Excretion) analysis and molecular docking studies were conducted to assess drug-like properties and binding affinities of selected compounds against bacterial target proteins (PDB IDs: 5M18 and 6NVU).ResultsThe genome of Streptomyces sp. VITGV156 was determined to be 8.18 Mb with a G+C content of 72.61%, containing 29 BGCs responsible for the biosynthesis of antimicrobial agents such as nystatin and fluostatins. In vitro antimicrobial assays confirmed strong efficacy of crude extracts against various pathogens, with Escherichia coli exhibiting the highest susceptibility. Molecular docking studies of 45 identified secondary metabolites revealed binding affinities ranging from -4.0 to -7.5 kcal/mol (5M18) and -3.9 to -7.2 kcal/mol (6NVU). Among the identified compounds, squalene (ligand 43) displayed potent antibacterial and antifungal activity, whereas 2,5-piperazinedione, 3-(hydroxymethyl)-6-(phenylmethyl)- (ligand 40) exhibited strong antifungal potential. Conversely, fumaric acid, monoamide, N-benzyl-N-phenylethyl-, ethyl ester (ligand 38) demonstrated weak antifungal activity.DiscussionThe genomic and bioactive analysis of Streptomyces sp. VITGV156 highlights its potential as a valuable source of novel antimicrobial agents. The identification of unique biosynthetic genes and bioactive secondary metabolites suggests its possible application in combating multidrug-resistant pathogens. Further studies, including purification and in vivo testing, are necessary to validate these findings and explore their therapeutic potential